Efecto del valor agregado bruto al costo de los factores y del crecimiento de la población urbana en el aumento de los gases de efecto invernadero: Un estudio con datos panel a nivel global utilizando técnicas de cointegración y causalidad, periodo 1990-2018 - Balcázar Cueva, Yordi David (2022)
The impact that human activity has had on the environment throughout history has been of great magnitude and the analysis of this relationship has hardly taken on importance since a few years ago. Considering the current problem, this research has the general objective of examining the effect of value added at the cost of factors and urbanization on greenhouse gases worldwide, through an econometric study using cointegration and causality techniques with data from panel in the period 1990-2018. For this, the postulates of the Kuznets environmental hypothesis were taken as a theoretical basis in a sample of 80 countries in the world divided by income groups, whose data were obtained from the World Bank database (2021) and PRIMAPhist (2021). The results obtained through the Westerlund (2007), Pedroni (1999) and Pedroni (2001) tests, allowed us to verify that there is a long-term relationship between gross value added, urbanization and non-renewable energy consumption, these being significant. to explain the increase in the levels of environmental contamination of most of the groups analyzed. Therefore, the existence of the environmental hypothesis is rejected, and it is mentioned as main recommendations, to strengthen international cooperation ties with respect to climate change and technological support programs, the application of carbon footprint monitoring systems, as well as articulated economic planning between urban and rural with long-term perspectives.